Preparation of high activity Ga and Cu doped ZnS by hydrothermal method for hydrogen production under visible light irradiation - Kimi, Melody (Hindawi Publishing Corporation, 2015)
Ga(0.1),Cu(x)-ZnS (x=0.01, 0.03, 0.05) photocatalysts were successfully synthesized by hydrothermal method. The synthesized Ga and Cu codoped ZnS photocatalysts showed photocatalytic property effective for hydrogen production from aqueous solution containing Na2SO3 and Na2S as sacrificial reagent under visible light irradiation. The rate of hydrogen production was found to be strongly dependent on Cu doping content. The highest photocatalytic activity is observed for Ga(0.1),Cu(0.01)-ZnS with hydrogen production rate of 114 μmol/h. The addition of Ga as codoped increased the photocatalytic activity to 58 times as compared to single doped Cu-ZnS. The Ga and Cu codoped ZnS photocatalysts are also stable under long irradiation. The enhancement in the photocatalytic activity of Ga and Cu codoped photocatalyst can be attributed to the synergistic effect between Ga and Cu. The photocatalytic activity was greatly enhanced with the addition of 0.5 wt% Ru as cocatalyst with a hydrogen production rate of 744 μmol/h. © 2015 Melody Kimi et al.